Enhancing modern contraceptive practices through web-delivered and printed health education module among married female staff in Universiti Putra Malaysia - Sharj Abad, Fatemeh Najafi (2014)
In spite of the widely available family planning services in Malaysia during past three decades, the contraceptive prevalence rate (CPR) has a steady rate, only 34% of women use modern contraceptive methods. The aim of this cluster randomized controlled trial study was to evaluate the effect of web delivered and printed health educational module on improving reproductive health knowledge, beliefs, spousal communication, perceived social support and practices on modern contraceptive methods for preventing unintended pregnancy among married female staff in UPM. Multistage random sampling was used for selection of faculties. The UPM area was divided to three zones and then randomly assigned to one of intervention or control zone. Then from each respective zone three faculties were selected. Baseline data collection on socio-demographic, marriage and reproductive health backgrounds,reproductive health knowledge, contraceptive beliefs, family planning spousal communication, perceived social support and practices on modern contraceptive methods were collected from the staff. A translated, reliable and valid tool based on Health Belief Model (HBM) was used to determine women’s perception on using modern contraception for preventing pregnancy. Reproductive health education modules adapted based on World Health Organization Guideline for Family Planning and delivered through website and booklet to the respective intervention groups during one month. A Family Planning Expert was introduced to the website to answer questions about women's reproductive health. For the booklet group, question and answer sessions were held by researcher at the work place. Both intervention groups received weekly reminder emails and tailored health messages for reading the module and motivation for contraceptive use during six months post intervention. The control group received the educational module only after the end of the study.Data were collected from control (n=127) and website (n=129) and booklet (n=130)at baseline, three and six months after end of intervention. Descriptive and multivariate statistics were used for analyzing the data using IBM, SPSS version 20. The mean age of respondents was 34.53 (SD=7.27) years and majority were Malay (96.1%) and Muslim (97.4%). Overall 36.8% used modern methods. Mistimed and unwanted pregnancies were reported by 22% and 11.4% of women respectively. One third of women experienced abortion. Between group comparison at 3 months showed there were significant differences in the mean score of reproductive health knowledge (0.002), perceived susceptibility (p=0.001), benefits (p=0.004), and self-efficacy (<0.001) between control and intervention groups. Between groups comparison at 6 months showed the proportion of modern contraceptive use was significantly different between control and intervention groups. There were significant differences in the mean score of all HBM variables, perceived susceptibility (p<0.001), severity (p<0.001), benefits (p<0.001),barriers (p=0.001), cue to action (p=0.01), contraceptive self-efficacy (p<0.001) at 6 months post intervention. There were significant differences in the mean score of reproductive health knowledge (p<0.001), perceived social support (p<0.001), and spousal communication (p<0.001) between control and intervention groups. Within group comparison showed among website the proportion of modern contraceptive use significantly increased over time (p=0.01). For website group from baseline to 6 months post intervention there were significant and consistent increase in the mean knowledge score (p<0.001), perceived susceptibility (p=0.002), severity (p=0.001), benefits (p=0.02), cue to action (p= 0.008), contraceptive self-efficacy (p=0.003), perceived social support (p=0.01) and decreased barriers for using modern contraception (p= 0.047). Within booklet from baseline to 6 months there were significant increase in the mean score of knowledge (p<0.001), perceived susceptibility (p=0.001), severity (p=0.005), benefits (p=0.015), self-efficacy (p=0.041) and social support (p=0.03). In the control group with the exception of reproductive health knowledge score which significantly changed from baseline to 6 months (p<0.001) no significant improvement was found in all other aspects. Webdelivered reproductive health education module which is accompanied by family planning counseling provide safe environment for discussing about sexual topics including contraceptive practices that is culturally sensitive among Malaysian educated women. At the end of study web-delivered health education intervention ,was more effective in decreasing barriers and improving modern contraceptives use,reproductive health knowledge, beliefs of educated married women in UPM as compared to printed reproductive health education module. Future family planning program need to be directed towards high risk cases, those with unmet needs for contraception and traditional contraceptive users to educate them regarding importance of family planning and choice of healthy timing and spacing of pregnancies.